Management of Long Bone Fractures with Intramedullary Interlocking Nailing (SIGN) at GMMMC Sukkur - KASHIF A. MEMON ZAMIR A, ZULFIQAR A. SOOMRO (Journal of Fatima Jinnah Medical University, 2018)
Objective: To assess the outcome of the management of long bone fractures with intramedullary interlocking nailing SIGN (surgical implant generation network). Patients and Methods: This prospective study was carried out at Department of Orthopaedic GMMMC Sukkur from March 2009 to FEB 2011. Total number of 80 cases treated with open/closed reduction with SIGN Nailing, Surgical data base was used, radiographs were used to determine fracture characteristics, aligment and fracture healing. This includes those patients with fresh and old fractures, while patients with severe communition were excluded. Results: Male to female ratio was 3:1, age range 18 to 73.There were 73 closed and 7 open fractures, 9 cases of implant failure. There were 7 retrograde femurs, 47 anterograde femur, 25 tibia and 1 humerus. Interlocking was done in 100% of cases. Surgical duration was 60 to 120 minutes and hospital stay was 5 to 7 days post intervention. Complication included superficial infection in 5 cases, deep infection 2 cases and screws loosing 2 cases. Time to union averaged 18 weeks with union ratio of 95%. Conclusion: SIGN intramedullary nailing system is effect in treatment option for diaphyseal fracture in the developing world with good result of fracture healing and patients satisfaction with minimal complication ratio comparable result.